STUDI KELAYAKAN INSTALASI PENGOLAHAN LUMPUR TINJA KOTA SALATIGA - Nasrullah Nasrullah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Salatiga’s Faecal Sludge Treatment Installation is used for the treatment of faecal sludge which is collected from  the  septic  tank  before  it’s  discarded  to  the  environment.  The  purpose  is  to improve  the municipal  sanitation  health  condition.  Based  on  the  local  health  department  of Salatiga  in  2005, 79%  Salatiga’s  resident  has  using  septic  tank  facilities.  The  Faecal  Sludge Treatment was planned for the next 20 years with the capacity of 6 m3/day and supported by stabilization system basin. The feasibility study is conducted to determine weather the Faecal Sludge  Treatment  Installation  is  suitable or  not.  Some  aspects  such  as  financial,  social, economics  and  technical  aspect  are  important  to be  considered.    The  investment  cost  to establish  this  installation  is  IDR  722.207.600  (tax included).  From  the  investment  planning evaluation  report,  FSTI  is  not  supported  financially because  the  period  payback  had unreachable to the end of planning session, the internal rate of return hadn’t achieved to the lowest rate of interest and the benefit cost ratio is lower than 1 which is 0,98. However the FSTI still  can  be  operated  because  the  other  aspects  are  still  support  the  FSTI construction  plan, which is technical, social, economic and regulation aspects.